Associations between Green Space and Health in English Cities: An Ecological, Cross-Sectional Study - Bixby, Honor; Hodgson, Susan; Fortunato, Léa; Hansell, Anna; Fecht, Daniela (PLOS ONE, 2015)
Green space has been identified as a modifiable feature of the urban environment and associations with physiological and psychological health have been reported at the local level. This study aims to assess whether these associations between health and green space are transferable to a larger scale, with English cities as the unit of analysis. We used an ecological, cross-sectional study design. We classified satellite-based land cover data to quantify green space coverage for the 50 largest cities in England. We assessed associations between city green space coverage with risk of death from all causes, cardiovascular disease, lung cancer and suicide between 2002 and 2009 using Poisson regression with random effect. After adjustment for age, income deprivation and air pollution, we found that at the city level the risk of death from all causes and a priori selected causes, for men and women, did not significantly differ between the greenest and least green cities. These findings suggest that the local health effects of urban green space observed at the neighbourhood level in some studies do not transfer to the city level. Further work is needed to establish how urban residents interact with local green space, in order to ascertain the most relevant measures of green space.